Developing Qur’an-Based Islamic Financial Literacy: A Digital Educational Game Innovation for Generation Z - Humayra, Tara Aqila (Unisia, 2025)
The rapid development of the digital economy has significantly transformed the financial behavior of young Muslims. Generation Z, born into a technology-driven era, actively engages in digital transactions, online investments, and cashless payment systems. However, despite their high digital literacy, many lack an understanding of Islamic financial ethics and Qur’anic principles in economic activities. The increasing trends of online loans, impulsive consumption, and ignorance of halal–haram boundaries in financial practices indicate a low level of Islamic financial literacy among this generation. This study introduces an innovative approach through the development of a Qur’an-Based Digital Educational Game as a medium to enhance basic Islamic financial literacy among Generation Z. The innovation responds to the learning style of digital natives, who prefer interactive, visual, and experience-based learning environments. By integrating game-based learning with Qur’anic values such as the prohibition of riba (Qur’an 2:275–279), the virtue of honesty (Qur’an 83:1–3), and the obligation of zakat (Qur’an 9:103), the game aims to convey Islamic financial concepts in an engaging, ethical, and spiritually enriching way. A Systematic Literature Study (SLS) method is employed to examine scholarly works on the integration of Islamic values into digital education, Gen Z’s financial behavior, and strategies for strengthening Islamic financial literacy. The results highlight that embedding Qur’anic ethics into digital learning media effectively internalizes Islamic economic awareness, strengthens moral responsibility, and promotes sustainable and just financial behavior. The approach transforms financial learning from a purely cognitive process into a spiritual experience encouraging youth to view economic actions as both an act of worship and a form of social responsibility. Findings further affirm that the Qur’anic Educational Game serves as a bridge between revelation and digital reality. It helps the younger generation realize that true financial success in Islam is not defined by material gain but by honesty, justice, and barakah (divine blessing). This innovation contributes to strengthening the Islamic economic ecosystem in the digital era by harmonizing moral, spiritual, and technological aspects within one learning framework. In conclusion, the development of a Qur’an-based digital educational game represents a concrete step toward integrating faith and innovation in Islamic economic education. It offers a transformative model for nurturing digitally literate, financially responsible, and spiritually conscious Muslim youth.